Online Marketing and Packaging Innovation to Increase Purchase Intention in MSMEs “GIG’S BATIK” Yogyakarta - Audita Nuvriasari; Gumirlang Wicaksono; Laras Nartanti; Karis Melly Andriani; Eko Yulianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The community service program was carried out at MSMEs Gig's Batik in Yogyakarta. The purpose of this activity is to increase consumer buying interest in Gig's Batik so that it will have an impact on improving business performance. Methods of implementing activities through training and counseling. The results of community service are increased knowledge and skills of partners in developing promotional content through social media (Instagram and TikTOK), increased consumer interest in Gig's Batik products as indicated by the increased number of followers on social media, and increased consumer demand to package batik products in packaging. innovations produced during community service activities.